The Influence of Marketing Mix on Customers Satisfaction and Loyalty at Tirtania Waterpark Bogor - Muhammad Akmal Ikramudin; Saptono, Imam Teguh; Jahroh, Siti (Business Review and Case Studies, 2023)
Covid-19 has caused several tourist objects to experience a decrease in visits, sales, and temporary closure due to the lockdown policy. Tirtania Waterpark is a water tourism object providing services for water recreation rides and family entertainment venues experiencing a decline in visits. Therefore, this research aims to analyze the effect of the marketing mix which consists of 4C, namely co-creation, currency, communal activation, and conversation variables on visitor satisfaction and loyalty at Tirtania Waterpark. This research is a case study with a sample of 126 people who are visitors of Tirtania Waterpark. The sampling method in this study was purposive sampling using questionnaires distributed to Tirtania Waterpark visitors. This study used the Structural Equation Model (SEM) method to perform data analysis. The results of the study show that all the marketing mix 4C variables used affect the satisfaction of visitors to Tirtania Waterpark, satisfaction variable has a significant effect on consumer loyalty which is reflected by the willingness of consumers to make repeat visits. Several recommendations to increase Tirtania Waterpark customer loyalty are conducting regular surveys of visitors, dynamic pricing, adding options in purchasing tickets, conducting promotions through other parties, and implementing good relationship management. Keywords: customer loyalty, customer satisfaction, marketing mix 4C, structural equation model, tourist attraction